Blimp-1/PRDM1 and Hr3/RORβ specify the blue-sensitive photoreceptor subtype in Drosophila by repressing the hippo pathway - Bunker, Joseph; Bashir, Mhamed; Bailey, Sydney; Boodram, Pamela; Perry, Alexis; Delaney, Rory; Tsachaki, Maria; Sprecher, Simon G.; Nelson, Erik; Call, Gerald B.; Rister, Jens (Frontiers in Cell and Developmental Biology, 2023)
During terminal differentiation of the mammalian retina, transcription factors control binary cell fate decisions that generate functionally distinct subtypes of photoreceptor neurons. For instance, Otx2 and RORβ activate expression of the transcriptional repressor Blimp-1/PRDM1 that represses bipolar interneuron fate and promotes rod photoreceptor fate. Moreover, Otx2 and Crx promote expression of the nuclear receptor Nrl that promotes rod photoreceptor fate and represses cone photoreceptor fate. Mutations in these four transcription factors cause severe eye diseases such as retinitis pigmentosa. Here, we show that a post-mitotic binary fate decision in Drosophila color photoreceptor subtype specification requires ecdysone signaling and involves orthologs of these transcription factors: Drosophila Blimp-1/PRDM1 and Hr3/RORβ promote blue-sensitive (Rh5) photoreceptor fate and repress green-sensitive (Rh6) photoreceptor fate through the transcriptional repression of warts/LATS, the nexus of the phylogenetically conserved Hippo tumor suppressor pathway. Moreover, we identify a novel interaction between Blimp-1 and warts, whereby Blimp-1 represses a warts intronic enhancer in blue-sensitive photoreceptors and thereby gives rise to specific expression of warts in green-sensitive photoreceptors. Together, these results reveal that conserved transcriptional regulators play key roles in terminal cell fate decisions in both the Drosophila and mammalian retina, and the mechanistic insights further deepen our understanding of how Hippo pathway signaling is repurposed to control photoreceptor fates for Drosophila color vision.